2019
DOI: 10.1039/c9gc00116f
|View full text |Cite
|
Sign up to set email alerts
|

A rational design of a Pd-based catalyst with a metal–metal oxide interface influencing molecular oxygen in the aerobic oxidation of alcohols

Abstract: The Pd–PdO interface stabilized on the rGO surface is shown to be the key to achieve enhanced catalytic activity in oxidation of alcohols under O2 as the oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
4
33
1
Order By: Relevance
“…The binding energies of 337.5 and 342.8 eV were observed in the all catalysts were ascribed to Pd 2+ 3d5/2 and 3d3/2 split orbitals of PdO, respectively. Additionally, in the 5% Pd/C (Strem Chemicals) another two lower binding energies of 336.0 and 341.1 eV are assigned to 3d5/2 and 3d3/2 levels of metallic Pd (Pd 0 ), respectively, [12][13][14] again confirming that PdO and Pd exist in the 5% Pd/C (Strem Chemicals) but not in the other two catalysts.…”
Section: Palladium Catalyst Analysismentioning
confidence: 80%
“…The binding energies of 337.5 and 342.8 eV were observed in the all catalysts were ascribed to Pd 2+ 3d5/2 and 3d3/2 split orbitals of PdO, respectively. Additionally, in the 5% Pd/C (Strem Chemicals) another two lower binding energies of 336.0 and 341.1 eV are assigned to 3d5/2 and 3d3/2 levels of metallic Pd (Pd 0 ), respectively, [12][13][14] again confirming that PdO and Pd exist in the 5% Pd/C (Strem Chemicals) but not in the other two catalysts.…”
Section: Palladium Catalyst Analysismentioning
confidence: 80%
“…This is perhaps unexpected given the ability of a range of these secondary metals, such as Fe, Mn and Cu, to catalyse the decomposition of H 2 O 2 through Fenton or Fenton-like pathways [45,46]. However, it is possible that the limited degradation activity observed can be related to a combination of two factors (i) the choice of reaction conditions used to evaluate H 2 O 2 synthesis activity, with the in-situ formation of carbonic acid, through the dissolution of the CO 2 reactant gas diluent resulting in the stabilisation of H 2 O 2 and (ii) the modification of Pd oxidation states upon introduction of secondary metals, as observed via XPS analysis (Table S.3), with the formation of mixed domains of Pd 0 -Pd 2+ reported to offer enhanced catalytic efficacy in both H 2 O 2 synthesis [47,48] and aerobic oxidation reactions [49]. It should be noted that our analysis by XPS reveals that the introduction of Au, unlike the majority of the other transition metals, does not promote the formation of these mixed oxidation state domains, which may explain the enhanced rates of H 2 O 2 synthesis and degradation observed over this catalyst [50].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies showed that, for metal-supported catalysts, the particle size of metal NPs and the basicity of the supports are two determining factors in alcohol oxidation with molecular oxygen [16][17][18][19][20]. The metal NPs with a small size hold more coordinatively unsaturated metal atoms, which are highly catalytic active [16,17], while the enhancement of the basicity of the support can generally facilitate the activation of alcohol molecules and, thus, increase the reaction activity [18,20]. Therefore, the superior catalytic performance of Pd/NH 2 -LDH-NS to Pd/LDH and Pd/LDH-NS can be ascribed to its smaller particle size of Pd NPs and enhanced basicity.…”
Section: Characterization Of Pd-supported Catalystsmentioning
confidence: 99%
“…For Pd-based catalysts, their catalytic properties are highly dependent on the size of the supported Pd nanoparticles (Pd NPs), and small-sized Pd NPs with a high dispersion usually lead to a high activity [14][15][16][17]. The nature of the supports and the interaction between the supported Pd NPs and the supports have great influence on the size of the supported Pd NPs [18][19][20].…”
Section: Introductionmentioning
confidence: 99%